2020
DOI: 10.1097/sla.0000000000003471
|View full text |Cite
|
Sign up to set email alerts
|

Total Neoadjuvant Therapy in Rectal Cancer

Abstract: Background: The addition of induction chemotherapy to concomitant neoadjuvant chemoradiation in locally advanced rectal cancer could increase pathological downstaging and act on occult micrometastatic disease, leading ultimately to a better outcome. A systematic review was carried out of the existing literature on the treatment outcomes of total neoadjuvant therapy (TNT) on locally advanced rectal cancer. TNT was defined as chemotherapy using cycles of induction and/or consolidation in conjunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
135
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(147 citation statements)
references
References 37 publications
5
135
1
6
Order By: Relevance
“…In summary, and to the best of our knowledge, our study is the largest meta-analysis on RCTs comparing TNT with standard neoadjuvant treatment in LARC and the first to demonstrate a significant impact on survival based on controlled data. A previous meta-analysis [26] included 28 studies, but the majority were retrospective and non-controlled trials. Only five were RCTs and just two reported survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, and to the best of our knowledge, our study is the largest meta-analysis on RCTs comparing TNT with standard neoadjuvant treatment in LARC and the first to demonstrate a significant impact on survival based on controlled data. A previous meta-analysis [26] included 28 studies, but the majority were retrospective and non-controlled trials. Only five were RCTs and just two reported survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There was consensus that induction chemotherapy should be offered to patients, and this reflects recent literature [22][23][24]. In the setting of symptomatic diseases such as obstruction or fistulation due to local invasion, the majority recommended a diverting stoma before commencing chemotherapy on the basis that this might downstage nonresectable or borderline resectable tumours and increase R0 resection margin rates [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…An example of adding cytotoxic drugs was the CAO/ARO/AIO-04 multicenter study, which involved patients with LARC who received neoadjuvant chemoradiotherapy, surgery, and ACT with or without oxaliplatin, and demonstrated 3-year DFS rates of 75.9 and 71.2%, respectively (21). TNT has been evaluated in a meta-analysis which involved 28 studies and demonstrated 3-year DFS and OS rates of 67 and 78.9%, respectively, in patients receiving TNT for LARC (22). Our FORWARC study, which also used an intensified NCT regimen in the preoperative setting, showed that 3-year DFS rates for fluorouracil plus radiotherapy, mFOLFOX6 plus radiotherapy, and mFOLFOX6 alone, were 72.9, 77.2, and 73.5%, respectively (23).…”
Section: Discussionmentioning
confidence: 99%